RETRACTED: Comparative Evaluation of the Incidence of Postoperative Pulmonary Complications After Minimally Invasive Valve Surgery vs. Full Sternotomy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Propensity Score-Matched Studies - Mohamed, Mohamed Abdulkadir; Ding, Shuai; Ali Shah, Sayed Zulfiqar; Li, Rui; Dirie, Najib Isse; Cheng, Cai; Wei, Xiang (Frontiers in Cardiovascular Medicine, 2021)
Background: Postoperative pulmonary complications remain a leading cause of increased morbidity, mortality, longer hospital stays, and increased costs after cardiac surgery; therefore, our study aims to analyze whether minimally invasive valve surgery (MIVS) for both aortic and mitral valve can improve pulmonary function and reduce the incidence of postoperative pulmonary complications when compared with the full median sternotomy (FS) approach. Methods: A comprehensive systematic literature research was performed for studies comparing MIVS and FS up to February 2021. Randomized controlled trials (RCTs) and propensity score-matching (PSM) studies comparing early respiratory function and pulmonary complications after MIVS and FS were extracted and analyzed. Secondary outcomes included intra- and postoperative outcomes. Results: A total of 10,194 patients from 30 studies (6 RCTs and 24 PSM studies) were analyzed. Early mortality differed significantly between the groups (MIVS 1.2% vs FS 1.9%; p = 0.005). Compared with FS, MIVS significantly lowered the incidence of postoperative pulmonary complications (odds ratio 0.79, 95% confidence interval [0.67, 0.93]; p = 0.004) and improved early postoperative respiratory function status (mean difference -24.83 [-29.90, -19.76]; p < 0.00001). Blood transfusion amount was significantly lower after MIVS (p < 0.02), whereas cardiopulmonary bypass time and aortic cross-clamp time were significantly longer after MIVS (p < 0.00001). Conclusions: Our study showed that minimally invasive valve surgery decreases the incidence of postoperative pulmonary complications and improves postoperative respiratory function status.